Maternal factors influencing late entry into prenatal care: a stratified analysis by race or ethnicity and insurance status. (18th October 2019) - Baer, Rebecca J.; Altman, Molly R.; Oltman, Scott P.; Ryckman, Kelli K.; Chambers, Christina D.; Rand, Larry; Jelliffe-Pawlowski, Laura L.
Abstract: Objective: Examine factors influencing late (> sixth month of gestation) entry into prenatal care by race/ethnicity and insurance payer. Methods: The study population was drawn from singleton live births in California from 2007 to 2012 in the birth cohort file maintained by the California Office of Statewide Health Planning and Development, which includes linked birth certificate and mother and infant hospital discharge records. The sample was restricted to infants delivered between 20 and 44 weeks gestation. Logistic regression was used to calculate relative risks (RR) and 95% confidence intervals (CI) for factors influencing late entry into prenatal care. Maternal age, education, smoking, drug or alcohol abuse/dependence, mental illness, participation in the Women, Infants and Children's program and rural residence were evaluated for women entering prenatal care > sixth month of gestation compared with women entering < fourth month. Backwards stepwise logistic regression was used to create final multivariable models of risk and protective factors for late prenatal care entry for each race or ethnicity and insurance payer. Results: The sample included 2, 963, 888 women. The percent of women with late entry into prenatal care was consistently higher among women with public versus private insurance. Less than 1% of white non-Hispanic and Asian women with private insurance entered prenatal care late versus more than 4% of white non-Hispanic and black women with public insurance. After stratifying by race or ethnicity and insurance status, women less than 18 years of age were more likely to enter prenatal care late, with young Asian women with private insurance at the highest risk (15.6%; adjusted RR 7.4, 95%CI 5.3–10.5). Among all women with private insurance, > 12-year education or age >34 years at term reduced the likelihood of late prenatal care entry (adjusted RRs 0.5–0.7). Drugs and alcohol abuse/dependence and residing in a rural county were associated with increased risk of late prenatal care across all subgroups (adjusted RRs 1.3–3.8). Participation in the Women, Infants, and Children's program was associated with decreased risk of late prenatal care for women with public insurance (adjusted RRs 0.6–0.7), but increased risk for women with private insurance (adjusted RRs 1.4–2.1). Conclusions: The percent of women with late entry into prenatal care was consistently higher among women with public insurance. Younger women, women with <12-year education, those who used drugs or alcohol or resided in rural counties were more likely to enter prenatal care late, with Asian women <18 years at especially high risk. Participation in the Women, Infants, and Children's program and maternal age >34 years at delivery increased the likelihood of late prenatal care for some subgroups of women and decreased the likelihood for others. These findings can inform institutional factors influencing late prenatal care, especially among lower income women, and may assist efforts aimed at encouraging earlier entry into prenatal care. Rationale: Optimal prenatal care includes initiation before the 14th week of gestation. Beginning care in the first trimester provides an opportunity for sonographic pregnancy dating or confirmation with best accuracy, which can later prove critical for management of preterm labor, maternal or fetal complications, or prolonged pregnancy. In order to improve maternal and infant health by increasing the number of women seeking prenatal care in the first trimester, it is important to examine the drivers for late entry. Here, we examine factors influencing late (> sixth month of gestation) entry into prenatal care by race/ethnicity and insurance payer. We found the percent of women with late entry into prenatal care was consistently higher among women with public insurance. Younger women, women with <12-year education, those who used drugs or alcohol or resided in rural counties were more likely to enter prenatal care late, with Asian women <18 years at especially high risk. These findings can inform institutional factors influencing late prenatal care, especially among lower income women, and may assist efforts aimed at encouraging earlier entry into prenatal care.